Pathologically confirmed spontaneous regression of small cell lung cancer after computed tomography-guided percutaneous transthoracic needle biopsy followed by surgery - Madoka Goto; Koichi Fukumoto; Yasuhisa Ichikawa; Hideki Tsubouchi; Mika Uchiyama; Shoichi Mori (Surgical Case Reports, 2023)
Abstract Background Spontaneous regression of malignant tumors is a rare phenomenon, especially in primary lung cancer. The underlying mechanisms remain unclear, but they may often involve immunological mechanisms. Case presentation In January 2020, a 78-year-old female underwent examination during follow-up of interstitial pneumonia. Chest X-ray and computed tomography (CT) scan revealed a 1.2 × 1.2 cm nodule in the left lower lobe. Based on CT-guided percutaneous transthoracic needle biopsy (PTNB), it was diagnosed as small cell lung cancer (SCLC). Immunohistochemical staining showed that tumor cells were positive for CD56, synaptophysin, and chromogranin A. Twenty-three days after the CT-guided PTNB, repeat CT scan showed that the tumor size regressed to 0.6 × 0.6 cm. The tumor showed positive uptake in fluorodeoxyglucose (FDG) positron emission tomography (PET)–CT. The maximum standardized uptake value of the nodule was 2.24. PET–CT and enhanced magnetic resonance imaging of the brain showed no distant or lymph node metastasis. The patient’s preoperative disease was diagnosed as cT1aN0M0, stageIA1, SCLC. In March 2020, she underwent left lower lobectomy and mediastinal lymph node dissection. Pathological examination of the resected specimen showed that the small tumor cells were dense with a high nucleus to cytoplasm ratio, and the morphological diagnosis was small cell carcinoma. The resected tumor size regressed to 0.05 × 0.02 cm, and no lymph node metastasis was observed. Because it was extremely small, immunohistochemical staining could not be conducted. Active fibrosis and inflammation were present around the tumor. Finally, the patient was pathologically diagnosed as SCLC pT1miN0M0, stage IA1. The patient is alive without recurrence 23 months after surgery with no adjuvant therapy. Conclusions We present a rare surgical case of pathologically confirmed spontaneous regression of SCLC after CT-guided PTNB. Although spontaneous regression is extremely rare, we should recognize this phenomenon.